The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.5194/hess-17-533-2013
|View full text |Cite
|
Sign up to set email alerts
|

What can flux tracking teach us about water age distribution patterns and their temporal dynamics?

Abstract: Abstract. The complex interactions of runoff generation processes underlying the hydrological response of streams remain not entirely understood at the catchment scale. Extensive research has demonstrated the utility of tracers for both inferring flow path distributions and constraining model parameterizations. While useful, the common use of linearity assumptions, i.e. time invariance and complete mixing, in these studies provides only partial understanding of actual process dynamics. Here we use long-term (<… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
443
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(483 citation statements)
references
References 162 publications
18
443
0
3
Order By: Relevance
“…This is a reformulation of the Mater Equation for the residence time probability density function (pdf) in time-variable flow systems developed by . A similar description of analogous concepts was also provided by later works [van der Velde et al, 2012;Hrachowitz et al, 2013]. A graphical representation of the physical meaning of equations (2) and (3) is provided in Figure 1.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is a reformulation of the Mater Equation for the residence time probability density function (pdf) in time-variable flow systems developed by . A similar description of analogous concepts was also provided by later works [van der Velde et al, 2012;Hrachowitz et al, 2013]. A graphical representation of the physical meaning of equations (2) and (3) is provided in Figure 1.…”
Section: Methodsmentioning
confidence: 93%
“…[47] The theoretical tools employed in this paper combine several recent advancements [Botter et al, 2010Rinaldo et al, 2011;van der Velde et al, 2010avan der Velde et al, , 2012Hrachowitz et al, 2013] in our understanding of the nonstationary character of catchment TTDs and the role of age distributions in the chemical composition of runoff into a single useful application. Our aims are rather of methodological nature, as the application highlights key features of any model of catchment-scale transport processes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons is that this non-stationarity is not accounted for in the models commonly used in catchment TT research. In the last 5 years, an ever-growing number of studies has transferred its focus to assessing dynamic TT distributions (Hrachowitz et al, 2010(Hrachowitz et al, , 2013Roa-García and Weiler, 2010;Rinaldo et al, 2011;Cvetkovic et al, 2012;Heidbüchel et al, 2012Heidbüchel et al, , 2013McMillan et al, 2012;Tetzlaff et al, 2014;Birkel et al, 2015;Benettin et al, 2015;Harman, 2015;Klaus et al, 2015a;Kirchner, 2015). Most of these studies agreed on the importance of considering storage dynamics, because the RT distribution of storage water and the TT distribution of water transiting at the outlet of the catchment are likely to be very different.…”
Section: Introductionmentioning
confidence: 99%
“…Calibration of the models on chloride measurements did not yield as accurate results as those for stable isotopes at S1 and to a higher extent at S2, which may be attributed to the higher effects of evaporative enrichment on chloride. Based on flux tracking methods, Hrachowitz et al (2013) showed that processes such as evaporation can result in considerable biases in TT distribution estimates when using chloride as a tracer.…”
Section: Identification Of a Younger Component In Streamflowmentioning
confidence: 99%
“…Based on these premises, Fenicia et al (2008), Clark et al (2011), McMillan et al (2012, and Hrachowitz et al (2013) aimed to describe both the spatial organization of the catchment and the set of interactions between processes with an assembly of coupled storages (reservoirs) in the number and the organization necessary to give proper hydrological results without adding unwanted parametric complexity (e.g., Klemeš, 1986;Kirchner, 2006). Despite the simplification efforts, the process of adding physical rigor to their models led to quite complex systems.…”
Section: Introductionmentioning
confidence: 99%